The Effect of Hap Addition on the Physical and Mechanical Properties of Co-Cr-Mo/Hap Composites for Biomedical Apllications - Muhammad Zulhilmi Shukor (School of Metallurgy Engineering, University Malaysia Perlis, 2015)
This paper reports on the effect of HAP addition on the physical and mechanical properties of Co-Cr-Mo/HAP composites fabricates by powder metallurgy. Co-Cr-Mo is used in orthopedic because of its excellent biocompatibility when implanted to human or animal body. Hydroxyapatite (HAP) powders have been used as fillers because of its similarity to minerals constituents of bones and teeth makes it as the one of the most effective biocompatible materials.